Diderma laiseae (Didymiaceae, Physarales), a new species of Myxomycetes from Brazil - Moreira, Izabel Cristina; Leonardo-Silva, Lucas; Xavier-Santos, Solange (Phytotaxa, 2025)
We describe a new species, Diderma laiseae, based on detailed morphological analyses. The type material was collected in the field from dead wood and insect remains (coleoptera) within Floresta Nacional de Silvânia, a conservation unit in the Cerrado biome in the state of Goiás, Brazil. D. laiseae is distinguished by its sessile sporophores with prominent, robust transverse and longitudinal ridges that give it a rough appearance, reticular dehiscence caused by the rupture of ridges, and strongly warted spores with irregular lines. We provide a taxonomic description, photographs (optical microscope, stereomicroscope and scanning electron microscope), a comparison with similar species, and a dichotomous key to the species of Diderma occurring in Brazil.